Bank capital and uncertainty - Valencia, Fabian (Journal of Banking & Finance, 2016)
Financial frictions in raising external finance can induce banks to self-insure against future shocks through holding more bank capital. As uncertainty about future losses increases, the above reasoning implies that they would choose to increase their capital position. This paper tests this hypothesis in a dataset with U.S. Commercial Banks by exploiting a cross-sectional variation in uncertainty to explain the distribution of bank capital ratios. I find statistically significant and robust evidence in support of a self-insurance mechanism. A counterfactual experiment suggests that a decline in uncertainty to its lowest level generates an average reduction in bank capital ratios of up to 2 percentage points. Furthermore, uncertainty explains, on average, about half of banks regulatory capital buffers.